We need radical gameplay: some more replay value in Galloway’s gaming - Tavares, Roger (InfoDesign, 2009)
<img title="id_v6_n1_2009_68_75_tavares_150" src="http://www.infodesign.org.br/revista/public/site/images/fnunes/id_v6_n1_2009_68_75_tavares_150.jpg" alt="id_v6_n1_2009_68_75_tavares_150" width="95" height="150" /> Gaming: Essays on Algorithmic Culture Galloway, Alexander. Minneapolis: University of Minnesota Press, 2006. [ISBN: 0-8166-4851-4] Gaming, Alexander Galloway, is one of the most interesting books in the Game Culture and Game Design area. He considers the language of the game in their specificity, using other media for some scores and comparisons. Galloway brings a proposal to analysis methodology, historiographical surveys, analysis and examples very well selected and constructive criticism in areas of the game that have not yet developed properly, such as game art and social realism. A must-read for anyone understand the game from different points of view, large, but never superficial.